Entrevista com Benjamin Halligan - Conter, Marcelo Bergamin (Intexto, 2014)
Benjamin Halligan is Director of the Graduate Programme for the School of Media, Music and Performance at the University of Salford. His publications include Michael Reeves (Manchester University Press, 2003), Mark E. Smith and The Fall: Art, Music and Politics (Ashgate, 2010; co-edited with Michael Goddard), The Music Documentary: Acid Rock to Electropop (Routledge, 2013, co-edited with Rob Edgar and Kirsty Fairclough-Isaacs). He has published on disco music music and and science fiction, The Sarajevo Documentary School, Dušan Makavejev, Frank Zappa, Andrei Tarkovsky and the British Royal Family. Resonances: Noise and Contemporary Music, co-edited with Michael Goddard and Nicola Spelman, has been published by Bloomsbury in 2013, and is the companion volume to Reverberations: The Philsophy, Aesthetics and Politics of Noise (Continuum, 2013; co-edited with Michael Goddard and Paul Hegarty). The following interview occurred at The Cornerhouse, in the city of Manchester, England, in june 2013. Benjamin speaks about topics related to the two books he recently organized with co-workers at the University of Salford, Reverberations: the philosophy, aesthetics and politics of noise, and Resonances: noise and contemporary music.